Being impolite while pretending to be polite. The rupture of politeness conventions in electoral debates - Fernández García, Francisco (Círculo de Lingüística Aplicada a la Comunicación, 2016)
This paper is a part of a larger research that pursues a global understanding of impoliteness in face-to-face electoral debates. That research distinguishes three essential axes, three complementary analytical perspectives: functional strategies of impoliteness, linguistic-discursive mechanisms to implement them and social impacts of impolite acts. In this frame, the present work develops an in-depth analysis of a special category of mechanisms, namely the rupture of politeness conventions, a subgroup within postliteral implicit mechanisms. This subgroup acquires its identity by the fact of carrying out a linguistic action that is conventionally associated with a polite attitude, but doing it in a rhetorically insincere way: the consequence is that apparent politeness becomes impoliteness. Relevant aspects in the characterization of ruptures are isolated and, on this basis, it is developed a detailed analysis of three specific kinds of mechanisms in which ruptures take shape: using ironic statements, developing different forms of overpoliteness and adopting a falsely collaborative attitude toward the interlocutor. The analysis of that group of mechanisms takes into account, simultaneously, the other two axes of the main research, strategies and social impacts.